If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 20 = 5x + -4 Reorder the terms: 20 + 2x = 5x + -4 Reorder the terms: 20 + 2x = -4 + 5x Solving 20 + 2x = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 20 + 2x + -5x = -4 + 5x + -5x Combine like terms: 2x + -5x = -3x 20 + -3x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 20 + -3x = -4 + 0 20 + -3x = -4 Add '-20' to each side of the equation. 20 + -20 + -3x = -4 + -20 Combine like terms: 20 + -20 = 0 0 + -3x = -4 + -20 -3x = -4 + -20 Combine like terms: -4 + -20 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 12-423a-12= | | 77+13p-77= | | 43a+56-43a= | | 23b+16-23b= | | 3g+5g=8g | | (3x-1)(3x+3)=3x(3x+1) | | -11+48+11-48+12= | | 3x-7=8x-21 | | 86+65-14-65+14= | | 39-14-39+14-23= | | 67+12+16-67-26= | | 0-10y=-80 | | 8x-0=-80 | | M+0.9+0.5m=-2.1 | | x^3-6x-20=0 | | 2x^2+14x-3=0 | | (2x-6)+4=4x-22 | | 2x-6+4=4x-22 | | 2x-3+4=4x-22 | | 14-8x=199-43x | | 11-8x=73-22x | | 14x+(x-7)-(3x+11)=40 | | 5x-(2x+6)=24 | | 2x-6+4=22+4x | | 2x+155=12x-5 | | 76-3x=15x+20 | | 2x-3+4=22+4x | | x-17=29 | | 6x-3=13x-35 | | 6x+0=18 | | 6(0)+3y=18 | | x^2-y^2=(x-2y)(x^2+y^2) |